The value attitude of a person to their psychological health: approaches to the definition - V. M. Miniyarov; A. A. Shakurova (Вестник университета)
The article is devoted to identification of the main characteristics that constitute the concept “value attitude of a person to their psychological health” that was conducted on the basis of the analysis of domestic and foreign literature. Firstly, the characteristic “health” was highlighted which is a state of the body characterised by internal comfort providing various functions of vital activity, creating mental, social and physical well-being that forms the basis of life quality. Secondly, the authors defined the characteristic “psychological health” as a psychological state of internal well-being of a person which depends on the individual-personal characteristics of a human, on their views and attitudes, on the degree of satisfaction of their needs and implementation of their own life plans. It is also seen as the ability of a person to withstand various stresses, changes in life and the ability to recover after that. Thirdly, the characteristic “value” was outlined. It is ideological orientation of the individual which is formed by their ideas of ideals, moral standards of behaviour in everyday life and which determines the personal meaning. Fourthly, the characteristic “attitude” was also studied. It is a conscious, selective, experience-based psychological connection of a person with reality which is expressed in actions, reactions and experiences and is formed in the process of activity. The final characteristic of the considered concept was the “value attitude”. It is defined as a one-sided relationship between a subject and an object when the subject assess the objects of reality according to their certain moral criteria. Thus, on the basis of the analysis of domestic and foreign psychological and pedagogical approaches, the authors have formulated the definition of the concept “value attitude of a person to their psychological health”.